2019
DOI: 10.3389/fmicb.2019.01337
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime and Amoxicillin Increase Metabolism and Enhance Caspofungin Tolerance of Candida albicans Biofilms

Abstract: It is well known that prolonged antibiotic therapy alters the mucosal microbiota composition, increasing the risk of invasive fungal infection (IFI) in immunocompromised patients. The present study investigated the direct effect of β-lactam antibiotics cefepime (CEF) and amoxicillin (AMOX) on biofilm production by Candida albicans ATCC 10231. Antibacterials at the peak plasmatic concentration of each drug were tested against biofilms grown on polystyrene surfaces. Biofilms were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In addition, the average thickness of the V. parahaemolyticus biofilm was significantly correlated with the BIC for amikacin ( p < 0.05). Cordeiro et al demonstrated the enhanced antibiotic resistance of microbial cells after the treatment of Candida albicans with the β-lactam antibiotics cefepime and amoxicillin, and concluded that antibiotics stimulated biomass production and increased the biological volume and average thickness of these structures [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average thickness of the V. parahaemolyticus biofilm was significantly correlated with the BIC for amikacin ( p < 0.05). Cordeiro et al demonstrated the enhanced antibiotic resistance of microbial cells after the treatment of Candida albicans with the β-lactam antibiotics cefepime and amoxicillin, and concluded that antibiotics stimulated biomass production and increased the biological volume and average thickness of these structures [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of invasive fungal infections (IFIs) has tragically increased during the last twenty years, despite advances in methods of diagnosis [1,2]. Candida-related IFIs are linked to elevated morbidity and mortality, as well as a high cost of healthcare [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of invasive fungal infections (IFIs) has tragically increased during the last twenty years, despite advances in methods of diagnosis [1,2]. Candida-related IFIs are linked to elevated morbidity and mortality, as well as a high cost of healthcare [1,2]. Candida albicans is still the major species related to candidemia wide world; however, the diversity of other Candida species differs according geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…The β-lactam antibiotics, such as cefepime, amoxicillin, and vancomycin, can stimulate the in vitro planktonic growth of C. albicans in 96-well plates and in vivo virulence tested with Caenorhabditis elegans infection model ( Aguiar Cordeiro et al, 2018 ). Cefepime and amoxicillin also directly stimulate C. albicans metabolism and biofilm formation in 96-well plates, thereby enhancing antifungal tolerance ( Cordeiro et al, 2019 ). Gut bacteria treated with β-lactam antibiotics released significant amounts of peptidoglycan fragments, a procedure so called “a peptidoglycan storm” ( Tan et al, 2021 ), which strongly stimulated hyphal formation in C. albicans in vitro and in vivo ( Xu et al, 2008 ; Tan et al, 2021 ).…”
Section: Effect Of Broad-spectrum Antibiotics On C Albicansmentioning
confidence: 99%